2022
DOI: 10.1155/2022/5069254
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Scheme ToA‐RSSI and Variable Anchor Positions for Sensors Localization in 2D Environments

Abstract: To rich good accuracy in the 2D area for wireless sensor network (WSN) nodes, a localization method has to be selected. The objective of this paper is first to select which localization technique is required (Received Signal Strength Indicator (RSSI)) or (Time of Arrival (ToA)) against anchors placement in a 2D area. Depending on whether the anchor nodes are spaced or not and inspired by the idea of using the RSSI method for small distances and the ToA method for greater distances, we will show which method sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Then, the centroid algorithm is proposed through the end point optimization. In [46], it was analyzed that the RSSI distribution has a higher accuracy at a small distance, while the ToA method has a higher accuracy when RSSI is at a long distance. Therefore, a wireless sensor positioning method for TOA-RSSI for a 2D environment was proposed, and the analysis showed that the method had a significant effect.…”
Section: Optimization Based On Database Matching Methodsmentioning
confidence: 99%
“…Then, the centroid algorithm is proposed through the end point optimization. In [46], it was analyzed that the RSSI distribution has a higher accuracy at a small distance, while the ToA method has a higher accuracy when RSSI is at a long distance. Therefore, a wireless sensor positioning method for TOA-RSSI for a 2D environment was proposed, and the analysis showed that the method had a significant effect.…”
Section: Optimization Based On Database Matching Methodsmentioning
confidence: 99%
“…In the work presented MATLAB based simulation results are presented which as more accurated than LSSVR-based or RSSI-TOA-based localization methods. Zaldi and friends propose a method based on selection of the localization technique as RSSI or ToA based on the anchors [23]. The RSSI method is used for small distances and the ToA method is preferred for greater distances and call their method as Combined Advantages of ToA-RSSI (CA ToA-RSSI).…”
Section: Related Workmentioning
confidence: 99%
“…For simple scenarios, validation of a 2D ray-tracer has been proved by comparison with measured data [37]. The ray-tracing technique is also used to generate multipath fingerprints for localization methods based on DOA, time difference of arrival or received signal strength [38][39][40]. However, real-time ray-tracing calculation is time-consuming in complex environments because of its high computational complexity.…”
Section: Introductionmentioning
confidence: 99%